IAPs, regulators of innate immunity and inflammation. (March 2015) - Estornes, Yann; Bertrand, Mathieu J.M.
Highlights: The role of IAPs extends apoptosis inhibition. XIAP, cIAP1 and cIAP2 regulate innate immune responses downstream of various PRRs and TNFRs. IAPs regulate inflammatory responses through their E3 ubiquitin ligase activities. cIAP1/2 regulate both the canonical and the non-canonical NF-κB pathways. IAPs are inhibitors of necroptosis, or programmed necrosis. Abstract: As indicated by their name, members of the Inhibitor of APoptosis (IAP) family were first believed to be functionally restricted to apoptosis inhibition. It is now clear that IAPs have a much wider spectrum of action, and recent studies even suggest that some of its members primarily regulate inflammatory responses. Inflammation, the first response of the immune system to infection or tissue injury, is highly regulated by ubiquitylation – a posttranslational modification of proteins with various consequences. In this review, we focus on the recently reported functions of XIAP, cIAP1 and cIAP2 as ubiquitin ligases regulating innate immunity and inflammation.